Analisis Sistem Akuntansi Penggajian Pegawai UPT Pengawasan Ketenagakerjaan Wilayah 1 Medan - Uci Roito Anggina Nst; Nurlaila Nurlaila (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to find out how the Payroll Accounting System for employees at UPT Labor Inspection Region 1 Medan. The application of the method in this research is descriptive qualitative, which uses descriptive research with a qualitative approach. Based on the results of the research that has been explained, the functions related to the payroll accounting system at UPT Labor Inspection Region 1 Medan are in accordance with the theory of functions related to the payroll accounting system which have been explained as there are staffing functions, timekeeping functions, payroll making functions, accounting functions, financial functions . The accounting function, financial function, and payroll function are carried out by the Finance Sub-Division of the North Sumatra Province Manpower Office.